2017
DOI: 10.1017/jns.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and safety of the intake of bovine milk oligosaccharides extracted from cheese whey in healthy human adults

Abstract: Mechanistic research suggests a unique evolutionary relationship between complex milk oligosaccharides and cognate bifidobacteria enriched in breast-fed infants. Bovine milk oligosaccharides (BMO) were recently identified as structurally and functionally similar to human milk oligosaccharides. The present single-blind three-way crossover study is the first to determine the safety and tolerability of BMO consumption by healthy human participants (n 12) and its effects on faecal microbiota and microbial metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Future studies will likely probe further into the mechanistic details of OS functionalities, as well as evaluate the feasibility of supplementing these molecules into adult diets as therapeutics. The safety and tolerability of isolated milk OS for human consumption were recently evaluated in two independent studies and showed promising results, with even relatively high dosages being well-tolerated (76, 77). These studies could pave the way for the known metabolic impacts of BMOs to be further evaluated in human subjects, including in specialized applications such as infant formula production.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies will likely probe further into the mechanistic details of OS functionalities, as well as evaluate the feasibility of supplementing these molecules into adult diets as therapeutics. The safety and tolerability of isolated milk OS for human consumption were recently evaluated in two independent studies and showed promising results, with even relatively high dosages being well-tolerated (76, 77). These studies could pave the way for the known metabolic impacts of BMOs to be further evaluated in human subjects, including in specialized applications such as infant formula production.…”
Section: Resultsmentioning
confidence: 99%
“…A recent clinical study showed that consumption of BMOs by adult volunteers was remarkably well-tolerated, even at dosages of up to 35% of daily fiber intake (Smilowitz et al 2017). Additional studies have provided some mechanistic insight into possible benefits of BMO.…”
Section: Diets Supplemented With Exogenous Milk Oligosaccharidesmentioning
confidence: 99%
“…Bovine milk and whey oligosaccharide fractions were identified as potentially interesting prebiotics, as they contain functional oligosaccharides such as sialyllactoses, galactosyllactoses and N-acetylgalactosyllactose [ 32 , 33 , 34 ]. However, bovine milk contains relatively small amounts of oligosaccharides, making their enrichment for nutritional applications challenging.…”
Section: Introductionmentioning
confidence: 99%